РОЗРАХУНОК ФУНКЦІЇ ПЕРЕТВОРЕННЯ ЄМНІСНОГО СЕНСОРА РАДІАЛЬНОГО БИТТЯ ВАЛІВ ЗАСОБАМИ КОМП’ЮТЕРНОГО МОДЕЛЮВАННЯ - Березниченко , В.О. (Інститут електродинаміки Національної академії наук України, 2021)
The paper presents the results study the characteristics of capacitive beating sensors to optimize them by computer simulation tools using. A concentric capacitive sensor with high-potential and grounded electrodes was studied. In the course of the research, the expediency of using computer modeling tools by finite element analysis methods to study the metrological characteristics of sensors was shown. It is shown that the application of modeling makes it possible to reduce the time spent on studies of the transformation function and metrological characteristics. The picture of the distribution of equipotential lines of an electric field in a working backlash of the sensor has resulted. The simulation results make it possible to create a picture of equipotential lines by changing the distance between the total surface of the sensor electrodes and the grounded surface, simulating the surface of the shaft. The results of the definition of the response function are given. References 23, figures 5.